Preliminary validation and refinement of the psychedelic aesthetic experience questionnaire - Hooper, Jake F.; Ellingson, Jarrod M.; Hutchison, Kent E. (Frontiers in Psychology, 2025)
IntroductionAesthetic experiences under psychedelics are often described as vivid, emotionally powerful, and meaningful, yet they remain under-measured in psychometric research. This study aimed to refine and validate the Psychedelic Aesthetic Experience Questionnaire (PAEQ), a novel instrument designed to assess the aesthetic dimensions of acute psychedelic experiences.MethodsA total of 365 past-year psilocybin users completed an anonymous online survey assessing their most typical psychedelic experience. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted on split samples to examine the latent structure of the PAEQ. Reliability, convergent validity, and regression models predicting self-reported psychological outcomes were evaluated.ResultsEFA and CFA supported a four-factor structure reflecting sensory, affective, semantic, and flow dimensions. Internal consistency was high for the total scale (α = 0.90) and acceptable across subscales. Convergent validity was supported by strong correlations with MEQ (r = 0.69), EBI (r = 0.54), and PIS (r = 0.56). PAEQ scores modestly predicted improvements in sleep, pain, substance use, anxiety, depression, and quality of life following psychedelic use.DiscussionDespite some weaknesses, the PAEQ provides a psychometrically sound measure of aesthetic engagement during psychedelic experiences, a domain not fully captured by existing instruments. Its multidimensional structure grounded in the aesthetic triad and flow theory offers new avenues for assessing altered states of consciousness and their therapeutic relevance.ConclusionThe refined PAEQ is a valid tool for quantifying aesthetic aspects of psychedelic experiences and contributes to advancing empirical approaches for characterizing altered states of consciousness.